Ruptured Tubal Pregnancy with a Negative Urine Pregnancy Test and Serum Beta Human Chorionic Gonadotropin - Panwara Paritakul (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
A rare case of ruptured tubal pregnancy with a negative urine pregnancy test (UPT) and serum beta hCG was reported. The patient presented with massive intraperitoneal bleeding and hypovolumic shock. Despite the negative UPT, a rupture tubal pregnancy was ruled out and a consultation with the gynaecologist was not done. Exploratory laparotomy revealed massive hemoperitoneum with a 5-cm purplish mass at the right fallopian tube and the right salpingectomy was performed. The serum beta hCG was sent intraoperatively, and the result was 4.2 mIU/mL. The pathological report confirmed a tubal pregnancy containing a 0.5-cm embryo and chorionic villi.